2009
DOI: 10.1002/ccd.21900
|View full text |Cite
|
Sign up to set email alerts
|

Radial compression guided by mean artery pressure versus standard compression with a pneumatic device (RACOMAP)

Abstract: Use of pneumatic compression guided by MAP is safe and efficient, and it can significantly lower the incidence of radial artery occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 22 publications
3
67
0
10
Order By: Relevance
“…Another speculation might be that the arterial stiffness in hypertension may preclude the total interruption of flow during manual compression, thus providing adequate maintenance of perfusion. In other words, patent hemostasis, which has been shown to decrease the rate of RAO [26,27], might be the mechanism in our hypertensive patients.…”
Section: Discussionmentioning
confidence: 84%
“…Another speculation might be that the arterial stiffness in hypertension may preclude the total interruption of flow during manual compression, thus providing adequate maintenance of perfusion. In other words, patent hemostasis, which has been shown to decrease the rate of RAO [26,27], might be the mechanism in our hypertensive patients.…”
Section: Discussionmentioning
confidence: 84%
“…10,12 Furthermore, rates of RAO are higher with prolonged cannulation times, 20 -22 whereas RAO is reduced with anticoagulation 23 and nonocclusive hemostasis. 11,24,25 Direct support for the thrombotic hypothesis has come from recent studies that have confirmed the presence of radial artery thrombus on vascular ultrasound, 26 angiography, 27 and pathology. 28 Transradial catheterization can also negatively affect radial artery structure and function.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The intervention group had significantly less RAO than the control group, both at 24 hours (5% versus 12%, PϽ0.05) and at 1 month (1.8% versus 7.0%, PϽ0.05). The importance of patent hemostasis was confirmed in the Radial Compression Guided by Mean Artery Pressure Versus Standard Compression with a Pneumatic Device Trial (RACOMAP), 24 which tested the concept using the TR Band (Terumo Medical Corporation, Somerset, NJ), a device with an inflatable bladder that is used to apply differential amounts of pressure to the artery. Patients were randomly assigned to compression guided by mean arterial pressure (the TR Band bladder was inflated to mean arterial pressure) versus a control group that received a standard 15 cc of air in the bladder.…”
Section: Sheath Sizementioning
confidence: 99%
“…5000 IU heparin (or 70 IU/kg) is recommended, and most operators use an intraarterial route. Other potential predictive factors of RAO are procedural time, operators in their learning curve, arterial diameter ratio to the sheath and compression time and pressure [8,9]. Anatomical variations: a wire can be introduced into a remnant artery with a small arterial diameter (type 3) but failure to advance any catheter is the rule and the incidence of spasm is very high in such anatomy.…”
Section: Prevention Of Radial Artery Occlusion (Rao)mentioning
confidence: 99%
“…The amount of air inflated in the TR-band usually varies between 13 to 18 ml. A Spanish study [9] showed that when the amount of air inflated was guided by mean arterial pressure (mean air volume of 8.8 ml), significantly fewer RAO were observed than…”
Section: Figurementioning
confidence: 99%